Bloodstream infections among intestinal and multivisceral transplant recipients. Issue 4 (8th July 2021) - Spence, Amanda B.; Novick, Elizabeth; Natarajan, Madhuri; Burkhart, Natalie; Girlanda, Raffaele; Timpone, Joseph
Abstract: Objective: To examine the etiologies, risk factors, and microbiology of bloodstream infections (BSIs) among intestinal and multivisceral transplant recipients in the 2‐year post‐operative period. Methods: A retrospective medical record review of adult intestinal or multivisceral transplant recipients between 2003 and 2015. Descriptive statistics were used to describe cohort data. Logistic regression was used to assess factors related to BSIs using a backward selection process. Results: One‐hundred and six intestinal or multivisceral transplants were performed in 103 individuals. Fifty‐eight percent (n = 62) developed a BSI in the 2‐year post‐operative period with a median time to first BSI of 53 days (interquartile range [IQR] 15, 169). The majority of BSIs were catheter related 38% (n = 58) when the source was known. Common microbiological isolates included enterococcus 20% (n = 36/174), coagulase‐negative staphylococcus 14% (n = 23), and 12% Klebsiella spp (n = 21). Forty‐seven percent (n = 17) of the enterococci were resistant to vancomycin, and 14% (n = 10/70) of the gram negatives were extended spectrum beta‐lactamase (ESBL) producers. In adjusted analyses, (OR: 0.200 95% CI: 0.2, 0.514, P  = .009) men were less likely to have a BSI. Transplant recipient age, allograft type, comorbidities, rejection, and length of stay were not noted to be risk factors for development of BSIs in our cohort. Mortality at 2‐years post‐transplant was similar for those who did not develop a BSI and those that developed infection, P  = .5028. Conclusions: BSIs are a common complication of intestinal transplantation, and central venous catheters were a common source. Interventions such as early catheter removal should be implemented to prevent infections in this population. Female sex association with BSI requires further investigation.